Nanoplatforms Potentiated Ablation-Immune Synergistic Therapy through Improving Local Control and Suppressing Recurrent Metastasis - Zixuan Wei; Xiaoya Yu; Mao Huang; Liewei Wen; Cuixia Lu (MDPI AG, 2023)
Minimally invasive ablation has been widely applied for treatment of various solid tumors, including hepatocellular carcinoma, renal cell carcinoma, breast carcinomas, etc. In addition to removing the primary tumor lesion, ablative techniques are also capable of improving the anti-tumor immune response by inducing immunogenic tumor cell death and modulating the tumor immune microenvironment, which may be of great benefit to inhibit the recurrent metastasis of residual tumor. However, the short-acting activated anti-tumor immunity of post-ablation will rapidly reverse into an immunosuppressive state, and the recurrent metastasis owing to incomplete ablation is closely associated with a dismal prognosis for the patients. In recent years, numerous nanoplatforms have been developed to improve the local ablative effect through enhancing the targeting delivery and combining it with chemotherapy. Particularly, amplifying the anti-tumor immune stimulus signal, modulating the immunosuppressive microenvironment, and improving the anti-tumor immune response with the versatile nanoplatforms have heralded great application prospects for improving the local control and preventing tumor recurrence and distant metastasis. This review discusses recent advances in nanoplatform-potentiated ablation-immune synergistic tumor therapy, focusing on common ablation techniques including radiofrequency, microwave, laser, and high-intensity focused ultrasound ablation, cryoablation, and magnetic hyperthermia ablation, etc. We discuss the advantages and challenges of the corresponding therapies and propose possible directions for future research, which is expected to provide references for improving the traditional ablation efficacy.